Demorfologizacja rodzaju w liczbie mnogiej rzeczowników w Księgach o gospodarstwie Piotra Krescentyna (Kraków 1549, Helena Unglerowa) - Osiewicz, Marek (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The article is a continuation of the research on linguistic variance in the first Polish edition of Księgi o gospodarstwie by Piotr Krescentyn (Krakow 1549, Helena Unglerowa). The inflectional forms were analyzed: the dative, instrumental and locative of plural nouns. The investigated issues included: textual differentiation, scope and degree of normalization of the particular alterations. The results of the analysis were compared with the results of research on other texts from the first half of the 16th century. The conclusions are: a) the books certify the initial but advanced stage of the demorphologization process of gender in plural nouns; b) the text distribution of most variants is even, the discontinuous textual distribution is characterized by only three inflectional forms: koniem and ludziom in the dative case, -och in the instrumental of the plural form of masculines; c) the state certified in the books is in most categories convergent with the state certified in other texts, the exception is the form of the instrumental and locus of masculine and neuter nouns; d) in the analyzed area, Księgi show little convergence with the language of Glaber’s texts (preferring the forms: ludziem in the dative case, -ami in the instrumental case, occasional end-case -och in the locative of masculines).